The Impact of Augmented Reality and Live Streaming on Maybelline Makeup Purchase Decisions Among Female Students in Malang Raya - Herliana, Grace; Sin, Liem Gai (PT FORMOSA CENDEKIA GLOBAL, 2024)
Makeup purchases are increasingly made online driven by the growing use of digital technology, especially among Generation Z. This research evaluates the impact of augmented reality and live streaming on purchase decisions. Using a quantitative approach, data were collected via surveys from 133 female university students in Malang Raya who use Maybelline products. Analyzed through multiple linear regression findings show that augmented reality enhances purchasing decisions by allowing virtual product trials, which boosts consumer confidence. Live streaming enriches the experience with real-time interactions and product demos. The combined effect of augmented reality and live streaming significantly influences consumer preferences, highlighting the need for Maybelline to optimize these strategies to boost engagement and sales in the Malang Raya region.